Expression of a Heterologous Glutamate Dehydrogenase Gene in Lactococcus lactis Highly Improves the Conversion of Amino Acids to Aroma Compounds - Rijnen, Liesbeth (American Society for Microbiology, 2000)
The first step of amino acid degradation in lactococci is a transamination, which requires an α-keto acid as the amino group acceptor. We have previously shown that the level of available α-keto acid in semihard cheese is the first limiting factor for conversion of amino acids to aroma compounds, since aroma formation is greatly enhanced by adding α-ketoglutarate to cheese curd. In this study we introduced a heterologous catabolic glutamate dehydrogenase (GDH) gene into Lactococcus lactis so that this organism could produce α-ketoglutarate from glutamate, which is present at high levels in cheese. Then we evaluated the impact of GDH activity on amino acid conversion in in vitro tests and in a cheese model by using radiolabeled amino acids as tracers. The GDH-producing lactococcal strain degraded amino acids without added α-ketoglutarate to the same extent that the wild-type strain degraded amino acids with added α-ketoglutarate. Interestingly, the GDH-producing lactococcal strain produced a higher proportion of carboxylic acids, which are major aroma compounds. Our results demonstrated that a GDH-producing lactococcal strain could be used instead of adding α-ketoglutarate to improve aroma development in cheese.